Phylogenetic phytogeography of selected groups of seagrasses (Monocotylendoneae - Alismatales) based on analysing of genes 5.8S rRNA and RuBisCo large subunit - Anton A. Iurmanov (GEOGRAPHY, ENVIRONMENT, SUSTAINABILITY, 2022)
Seagrasses are representatives of the families Cymodoceaceae, Posidoniaceae, Zosteraceae, Hydrocharitaceae (Monocotylendoneae - Alismatales), adapted to growing in seawaters and all their important life circle events are taking place under the water including pollination and distribution of diasporas. Seagrasses are widespread in the littoral areas of the World Ocean, except for Antarctica, and play an important ecosystem role. Due to the insufficiently studied history of dispersal and formation of modern seagrasses habitats, we carried out a phylogenetic analysis of representatives of the families Cymodoceaceae (Amphibolis, Halodule, Syringodium, Cymodocea, and Thalassodendron), Posidoniaceae (Posidonia), Zosteraceae (Zostera, and Phyllospadix), and Hydrocharitaceae (Enhalus, Halophila, and Thalassia). The cladograms constructed based on molecular data analysis of the 5.8S ribosomal RNA and ribulose–1,5–bisphosphate carboxylase/oxygenase large subunit genes are used as the basis for reconstructing the history of dispersal of the studied taxa. It is found that the main stages of dispersal of selected groups of seagrasses took place in the Late Cretaceous period. The main track of historical distribution is largely predetermined by the modern ranges of almost all genera of seagrasses, stretches from the southwestern waters of eastern Gondwana to the northwestern waters of the Eurasian part of Laurasia. The main route of movement of diasporas and seagrasses populations was the Tethys water area, which was modified in the Late Mesozoic and early Cenozoic. It was revealed that the main method of dispersal of seagrasses was long-distance dispersal, which is confirmed by both molecular genetic data and very fast (on a geological time scale) processes of penetration into new water areas, and analysis of the features of dissemination of modern representatives. An alternative vicar scenario was proposed only for the reconstruction of the formation of the Posidonia range.